Más allá del medievalismo y el arabismo: Al-Ándalus en perspectiva poscolonial - García Fernández, Javier (2021)
This article aims to contribute to overcoming the Euro-centric and Occidentalist views of Al-Andalus through the critical analysis of two disciplines: medievalism and Arabism. First, medievalism is described as an exercise in Occidentalism. Secondly, Spanish Arabism is analysed as a discursive corpus originating in the French colonial world. The text concludes by incorporating certain contributions from Latin American decolonial theory and from contemporary Anglo-American postcolonial medievalism, to locate certain lines of analysis and reflection that call for a postcolonial and non-Eurocentric view of the Andalusian phenomenon.